Kekerasan terhadap Perempuan di Ruang Publik Kota Jayapura - H R Partino; Khairuddin N M (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2008)
Using qualitative approach, the aim of recent study was to explore the domestic violence on women in Jayapura. 500 subject were interviewed (50% from rural area and 50% from urban. The characteristics of the respondents are under 35 years in age, married and live with their own family. The result in general shows that women were sexually violated as well as non-sexually and the abusers are the ones who have been known by the victim. Moreover, this research also found out how the victims' responses to the assault. They tend to remain silence or running away. They did try to look for help but no significant defenses had been done against the abusers so far by the victims. Women from lower soda/ status which mostly from rural area reported the domestic violence they had been encountered to their family whilst ones from middle social status and mostly live in urban area reported the assault to the police or public authority.